Mechanisms of Prenatal Programing: Identifying and Distinguishing the Impact of Steroid Hormones - O’Connor, Thomas G.; Barrett, Emily S. (Frontiers in Endocrinology, 2014)
Developmental programming is gaining considerable leverage as a conceptual framework for understanding individual variability in human behavioral and somatic health. The current mini-review examines some of the key conceptual and methodological challenges for developmental programming research focused on fetal sex steroid exposure and physical, behavioral, physiological and health outcomes. Specifically, we consider the bases for focusing on sex steroids, methods for assessing prenatal steroid hormone exposure, confounding factors, and the the most relevant postnatal outcomes. We conclude with a brief consideration, based on current knowledge, of the applications of the existing research findings for practice.